A STUDY ON BIOMASS: a renewable source of clean energy - Roberto Martins, Luiz; Carrino, Adaulto Luiz (Revista Interface Tecnológica, 2023)
In Brazil, biomass is indeed a potential source of energy, simply because it is renewable energy, easily supplied and with an excellent energy return for those who use this energy. It is increasingly clear that this type of energy stands out for its energy potential, and also for its sustainability, which is undoubtedly very important for the planet itself. The world with the various changes that have occurred in time, the use of fuel sources was being left aside and the current moment is renewable energy sources, and much of this energy is due to the change in the world’s energy matrix. However, biomass is a set of organic matter, being vital for the direct and indirect foundation when we talk about bioenergy. Due to the large world energy consumption, biomass used with clean energy is essential to have other sustainable sources of energy, which with global energy maintenance, has been improved in technology and protection for better uses today and soon with processes more and more technological to obtain great performance and use of this clean energy.